An Efficient Load Balancing Approach For Resource Utilizations In Green Cloud Computing - Himanshu Sharma, Vijay Kumar Joshi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The green cloud solution not only reduces energy usage but also significantly lowers operational costs. The fundamental goal is to provide complete computing influence from a large collection of resources as a result significant computations occur in strongly tied data centers that require regulated energy and consistent performance with overall optimization of the excess energy consumption. The study uses green cloud technology and is centered on a scheduling mechanism for saving energy. The divisions are concerned with the high-efficiency structure wherein every business demands high homogeneity, flexibility, and effectiveness across multi-cloud scenarios. The developed study focuses on reducing energy usage in green cloud systems using a hybrid scheduling technique that includes a priority-based weighted round-robin and minimum completion time. To balance the the requests, performance is assessed for low error rates and power effectiveness. It has been noticed that our developed approach can achieve better performance as compared to other techniques which are implemented to compare and validate the performance.